Crystallization behavior of poly(lactic acid) and its blends. Issue 3 (31st December 2020) - Wang, Yaming; Liu, Chuntai; Shen, Changyu
Abstract: Poly(lactic acid) (PLA) is one of the most interesting bio‐based biodegradable alternatives, with great promise to replace petroleum‐based plastics. However, the intrinsic slow crystallization ability of PLA restricts its extensive applications. In this perspective, we highlight some recent advances in PLA crystallization, including nucleation by self‐assembly nucleating agents, self‐nucleation (or memory effect), conformational ordering in the very early stage of crystallization, crystal nucleation investigated by fast scanning calorimetry (Flash DSC), crystallization under flow, and pressure fields, and crystallization of enantiomeric blends. Finally, major challenges and future perspectives are proposed. Abstract : Poly(lactic acid) (PLA) is one of the most interesting biobased biodegradable polyesters. However, the intrinsic slow crystallization ability restricts its extensive applications. In this perspective, some recent advances in PLA crystallization are highlighted, including nucleation by self‐assembly nucleating agents, self‐nucleation, conformational ordering in the very early stage of crystallization, crystal nucleation investigated by fast scanning calorimetry, crystallization under flow and pressure fields, and crystallization of enantiomeric blends. Finally, major challenges and future perspectives are proposed.